Sex and tissue‐specific evolution of developmental plasticity in Drosophila melanogaster - Sarikaya, Didem P. (John Wiley and Sons Inc., 2020)

(untitled) (Ecol Evol)
Developmental plasticity influences the size of adult tissues in insects. Tissues can have unique responses to environmental perturbation during development; however, the prevalence of within species evolution of tissue‐specific developmental plasticity remains unclear. To address this, we studied the effects of temperature and nutrition on wing and femur size in D. melanogaster populations from a temperate and tropical region. Wings were more sensitive to temperature, while wings and femurs were equally responsive to nutrition in both populations and sexes. The temperate population was larger under all conditions, except for femurs of starved females. In line with this, we observed greater femur size plasticity in response to starvation in temperate females, leading to differences in sexual dimorphism between populations such that the slope of the reaction norm of sexual dimorphism in the tropical population was double that of the temperate population. Lastly, we observed a significant trend for steeper slopes of reaction norms in temperate than in tropical females, but not in males. These findings highlight that plasticity divergence between populations can evolve heterogeneously across sexes and tissues and that nutritional plasticity can alter sexual dimorphism in D. melanogaster.